2012
DOI: 10.1111/jfpp.12001
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Pre-Fry Microwave Drying of French Fries Using Response Surface Methodology and Genetic Algorithms

Abstract: In this study, microwave pretreatment and frying conditions optimized with respect to quality attributes (moisture content, oil content, texture and color parameters) and tried to investigate the efficiency of genetic algorithms (GA) for improving response surface methodology (RSM) models. RSM technique was used to develop models to respond to the microwave power (180, 360, 540 W), microwave time (2, 3, 4 min), frying temperature (140, 160, 180C) and frying time (2, 5, 8 min). Microwave pretreatment had a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…[154] Similar results were found for microwave pre-treated deep-fat fried chicken nuggets, where the microwave treatment had a significant effect in reducing moisture loss and oil uptake during subsequent frying steps. [155] Microwave energy was applied during frying in the case of potato slices, where it was found that the oil uptake was lower than those fried conventionally.…”
Section: Operationssupporting
confidence: 84%
“…[154] Similar results were found for microwave pre-treated deep-fat fried chicken nuggets, where the microwave treatment had a significant effect in reducing moisture loss and oil uptake during subsequent frying steps. [155] Microwave energy was applied during frying in the case of potato slices, where it was found that the oil uptake was lower than those fried conventionally.…”
Section: Operationssupporting
confidence: 84%
“…During optimization of oil extraction condition, response variables relating to quality are usually to be optimized. Finally among different suggested conditions, a point that maximizes the desirability function was selected (numerical optimization) (Hashemi Shahraki, Ziaiifar, Kashaninejad, & Ghorbani, ).…”
Section: Methodsmentioning
confidence: 99%
“…A central composite design with six central points was used to optimize the physical properties of almond milk . In this work's hypothesis, the physical properties (Brix, physical stability, lightness, yellowness, viscosity and particle size) of almond milk were functionally related to US time; amounts of modified starch, lecithin and agar; and attempts that were made to fit multiple regression equations describing the responses (Hashemi Shahraki et al 2014b). There were four coded independent variables including US time (X1), amounts of lecithin (X2), modified starch (X3) and agar (X4) ( Table 2).…”
Section: Optimization Proceduresmentioning
confidence: 99%